2011
DOI: 10.1111/j.1364-3703.2011.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Top 10 plant viruses in molecular plant pathology

Abstract: Many scientists, if not all, feel that their particular plant virus should appear in any list of the most important plant viruses. However, to our knowledge, no such list exists. The aim of this review was to survey all plant virologists with an association with Molecular Plant Pathology and ask them to nominate which plant viruses they would place in a 'Top 10' based on scientific/economic importance. The survey generated more than 250 votes from the international community, and allowed the generation of a To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
606
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 994 publications
(675 citation statements)
references
References 188 publications
0
606
0
19
Order By: Relevance
“…Plum pox virus (PPV) belongs to a group of 'Top 10' plant viruses in molecular plant pathology based on their perceived scientific or economic importance (Scholthof et al, 2011). PPV causes Sharka, the most deleterious viral disease of stone fruits that infects many commercial, ornamental and wild species in the genus Prunus.…”
Section: Introductionmentioning
confidence: 99%
“…Plum pox virus (PPV) belongs to a group of 'Top 10' plant viruses in molecular plant pathology based on their perceived scientific or economic importance (Scholthof et al, 2011). PPV causes Sharka, the most deleterious viral disease of stone fruits that infects many commercial, ornamental and wild species in the genus Prunus.…”
Section: Introductionmentioning
confidence: 99%
“…With the global invasion of MEAM1 and MED whiteflies, many economic crops are at great risk of infection with begomoviruses (15,18,19). Among these viruses, Tomato yellow leaf curl virus (TYLCV) is one of the most devastating viral diseases and has spread to more than 50 countries and regions (20,21). Interestingly, although most of the studies reported an absence or low frequency of transovarial transmission in begomoviruses, one case reported that TYLCV can be transovarially transmitted at high efficiency (22) (Table S1).…”
mentioning
confidence: 99%
“…PVY infects a broad range of plants in the Solanaceae family, including important agricultural crops such as potatoes, tobacco, tomato, pepper, and petunia (Kerlan and Moury 2006). PVY is a Potyvirus with a 9.7 kb positive sense single-stranded RNA genome and a filamentous capsid (11 nm diameter × 740 nm length) (Scholthof et al 2011). Mutation and recombination have resulted in a great diversity of PVY strains worldwide (MacKenzie et al 2015).…”
Section: Introductionmentioning
confidence: 99%